2018
DOI: 10.17576/jskm-2018-1602-05
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Assessment of Food Contact Surfaces in Residential College Cafeterias at a Local University in Malaysia

Abstract: A food premise's sanitation level can be reflected by the cleanliness of its food contact surfaces. Contaminated food contact surfaces along with poor handling methods by food handlers may increase the risk of foodborne diseases through cross-contamination events. This study aimed to assess the microbiological contamination levels on food contact surfaces of 12 residential college cafeterias in a local university and its correlation with the cafeteria's premise grade. The presence of selected indicator and pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
(16 reference statements)
1
4
0
1
Order By: Relevance
“…World Health Organization (WHO) stated that presence of one E. coli and greater than 10 coliforms renders water unsatisfactory for drinking by humans and animals (WHO, 2011). The result is similar to those of Zulfakar et al (2018) in Malaysia who obtained the total coliform of 2.52 ± 0.52 log CFU/cm 2 in Cafeteria K and 0.36 ± 0.11 log cfu/cm 2 in Cafeteria F at a local University. In contrast Nhlapo et al (2014) in South Africa showed the 60% of the counts obtained from hands to be satisfactory while 20% were acceptable and 20% were not detectable.…”
Section: Antibiogram Of the E Coli And S Aureus Isolatessupporting
confidence: 88%
See 1 more Smart Citation
“…World Health Organization (WHO) stated that presence of one E. coli and greater than 10 coliforms renders water unsatisfactory for drinking by humans and animals (WHO, 2011). The result is similar to those of Zulfakar et al (2018) in Malaysia who obtained the total coliform of 2.52 ± 0.52 log CFU/cm 2 in Cafeteria K and 0.36 ± 0.11 log cfu/cm 2 in Cafeteria F at a local University. In contrast Nhlapo et al (2014) in South Africa showed the 60% of the counts obtained from hands to be satisfactory while 20% were acceptable and 20% were not detectable.…”
Section: Antibiogram Of the E Coli And S Aureus Isolatessupporting
confidence: 88%
“…Food borne pathogens such as Staphylococcus aureus, Escherichia coli O157:H7, Salmonella typhi and parathyphi, Shigella spp., Vibrio cholerae 01, Streptococcus pyogenes, Entamoeba histolytica, Yersinias enterocolitica, Giardia lamblia, Campylobacter jejuni, Cryptosporidium parvum, Caliciviruses (norovirus, Hepatitis A virus and host of others have been associated with food poisoning outbreaks (FDA, 2014;Ayalew et al, 2015). Although food contact surfaces has been an interest for many studies in Nigeria and other parts of the world, little information on their safety and microbial status is available in the study area (Oranusi et al, 2013;Lani et al, 2014;Ayalew et al, 2015;Zailani et al, 2015;Zulfakar et al, 2018). This necessitated the present study to assess the microbial quality of food contact surfaces, to isolate and identify Escherichia coli and Staphylococcus aureus and to determine the antibiogram of the E. coli and S. aureus isolated from food contact surfaces in restaurants and food canteens in Ahmadu Bello University Main Campus, Samaru, Zaria, Kaduna State.…”
Section: Introductionmentioning
confidence: 99%
“…Other sources of microbial contamination in street-vended beverages were the occurrence of cross-contamination between food or surfaces contaminated by bacteria with the beverages. Food contact surfaces may still harbor a high number of bacterial cells despite their clean appearances [34]. All street food vendors should ensure that all equipment, utensils, and other food contact surfaces that are regularly cleaned and kept in hygienic conditions during their operations [1].…”
Section: Discussionmentioning
confidence: 99%
“…The process of slaughtering animals to meat processing are usually conducted in the market according to Syariah law. Collection of meat contact surface samples were conducted as previously described by Zulfakar et al (2018). In general, sterile sponge swabs (3M, USA) were moistened with sterile buffered peptone water (Merck, Darmstadt, Germany).…”
Section: Sample Collectionmentioning
confidence: 99%
“…Meat contact surfaces are usually contaminated with pathogens from the intestinal tract, feet and feathers of animals. Combination of contaminated food contact surfaces and low hygienic practices by the food handlers increases the risk for a foodborne disease (Zulfakar et al 2018). Proper handling of poultry meat is important in order to ensure hygienic monitoring of processed meat and meat contact surfaces in retail production (Saad et al 2011).…”
Section: Introductionmentioning
confidence: 99%